IMPACT OF PREGNANCY ON THE ACTIVITY OF RHEUMATOID ARTHRITIS AND ITS THERAPY ACCORDING TO PROSPECTIVE FOLLOW-UP DATA - E. V. Matyanova; N. M. Kosheleva; Z. S. Alekberova; E. N. Aleksandrova (Научно-практическая ревматология, 2015)
Rheumatoid arthritis (RA) frequently affects women of child-bearing age, which determines long-standing interest in studying the mutual impact of pregnancy and RA. The first observation described about 80 years ago has shown decrease of disease activity in the absolute majority of pregnant women. Later prospective studies have demonstrated that only 48–66% of women have clinical improvement during pregnancy, postpartum exacerbation of RA develops in 70% of cases, and most patients need drug therapy.Objective: to assess changes of RA activity with DAS28-CRP during pregnancy and postpartum; to examine the impact of RA activity during early pregnancy on further course of the disease; and to determine drug therapy requirement in pregnant women with RA.Subjects and methods. Thirty-two pregnancies were prospectively followed up during each trimester and within 12 months postpartum in 29 women with RA who fulfilled the 1987 ACR criteria and had been examined at the V.A. Nasonova Research Institute of Rheumatology from February 2011 to August 2014.Results and discussion. 46% of the patients with RA showed reduction of disease activity during pregnancy. Exacerbation of RA was observed in 75% of the patients within 12 months at 1.5 months postpartum on average. In patients who were in remission and had low disease activity during early pregnancy, activity of RA throughout pregnancy and 1 month postpartum remained lower than that in those with moderate and high activity in the first trimester (p = 0.0008–0.04). A similar trend was also seen in patients without active arthritis at the moment of conception (according to survey data). In 23 (71.9%) patients with signs of disease activity during pregnancy, anti-inflammatory therapy was enhanced and DAS28-CRP decreased (p = 0.008) while it tended to increase in the remaining 9 (28.9%) patients with low disease activity who did not received medication. After delivery, patients with high and moderate disease activity showed earlier improvement (p = 0.008), as they more early resumed therapy with diseasemodifying antirheumatic drugs (DMARDs) and biologics than those who were in remission and had low disease activity during pregnancy. In the latter, a tendency for higher disease activity persisted for 3 months after delivery. Disease activity during the first-to-third trimester was significantly higher in 12 (37.5%) patients who had conceived while taking DMARDs or biologics and urgently withdrew them due to their pregnancy than in 20 (62.5%) cases when DMARDs and/or biologicalshad not been used or had been discontinued in advance when they started planning pregnancy (p < 0.04).Conclusion. Remission or low activity of RA during early pregnancy is a predictor for low disease activity and for minimizing drug therapy to the point of its refusal throughout pregnancy. Without drug therapy, RA activity may tend to increase. A postpartum RA exacerbation is also noted in patients who have been in remission and had low RA activity antepartum. Dramatic withdrawal of DMARDs or biologics because of an unplanned pregnancy contributes to higher RA activity just in the first trimester of pregnancy. Pregnancy should be planned, by choosing stable anti-inflammatorytherapy in advance.